Community Based Warning and Evacuation System against Debris Flow in the Upper Jeneberang River, Gowa, South Sulawesi - Sutikno Hardjosuwarno (Universitas Muhammadiyah Surakarta, 2008)
Gigantic collapse of the Caldera wall of Mt. Bawakaraeng (2,830 m) in March 2004 had supplied the sediment volume of 230 million to the most upper stream of Jeneberang River, which flowed down to the lower reach in the form of debris flow which is triggered by rainfall. The purpose of the research is to provide a system which is able to forecast the occurrence of debris flow, to identify the weak points along the river course, to identify the hazard areas and how to inform effectively and efficiently the warning messages to the inhabitants in the dangerous area by using the existing modern equipment combined with the traditional one. The standard rainfall which is used to judge the occurrence of debris flow was established by Yano method. It is based on the historical data of rainfall that trigger and not trigger to the occurrence of debris flow which is widely used in Japan so far. The hazard area was estimated by Two-Dimensional Simulation Model for debris flow, the debris flow arrival time at each point in the river were estimated by dividing their distance from reference point by debris flow velocity, where the check dam no. 7-1 in Manimbahoi was designated as reference point. The existing evacuation routes were checked by field survey, the strength and coverage of sound for kentongan and manual siren were examined using sound pressure level at the location of the existing monitoring post and the effectiveness of warning and evacuation were evaluated by comparing the warning and evacuation time against the debris flow arrival time. It was resulted that debris flow occurrence was triggered by short duration of high rainfall intensity, long duration of low rainfall intensity and the outbreak of natural dam which is formed by land slide or bank collapses. The hazard area of upper Jeneberang River are mostly located on the river terraces where the local inhabitants earn their living through cultivating the river terraces as paddy fields, dry field and sand mining. It was also resulted that at the elevation of 700 m to the upper stream, the arrival time of debris flow is too short ( 3 minutes), it means that there is no time to evacuate when debris flow occurs. There are enough time to evacuate along the reaches between 700 m to 390 m and more time to evacuate along the downstream of 390 m river bed elevation due to the longer arrival time of debris flow. The existing community based warning system against debris flow uses radio transceiver to communicate between post and uses kentongan and sirens to propagate the warning message to inhabitants. Based on the sound test conducted in Jeneberang River, the manual siren has a coverage of 160 m to 600 m and it can be used in the warning system, being co-existence with the kentongan which has been used for a long time. In order to keep the community based warning system well functioned, it is recommended to synergize between the Local Government of Gowa Regency and the other stake holders with the inhabitants along Jeneberang River and the Sabo Community of Jeneberang in the operation and maintenance of the system.